Effect of partial grooving on the performance of hydrodynamic journal bearing. Issue 4 (10th July 2017) - Shinde, Anil B.; Pawar, Prashant M.
Abstract : Purpose: This study aims to improve the performance of hydrodynamic journal bearings through partial grooving on the bearing surface. Design/methodology/approach: Bearing performance analysis is numerically carried out using the thin film flow physics of COMSOL Multiphysics 5.0 software. Initially, the static performance analysis is carried out for hydrodynamic journal bearing system with smooth surface, and the results of the same are validated with results from the literature. In the later part of the paper, the partial rectangular shape micro-textures are modeled on bearing surface. The effects of partial groove pattern on the bearing performance parameters, namely, fluid film pressure, load carrying capacity, frictional power loss and frictional torque, are studied in detail. Findings: The numerical results show that the values of maximum fluid film pressure, load carrying capacity, frictional power loss and frictional torque are considerably improved due to deterministic micro-textures. Bearing surface with partial groove along 90°-180° region results in 81.9 per cent improvement in maximum fluid film pressure and 75.9 per cent improvement in load carrying capacity as compared with smooth surface of journal bearing, with no increase in frictional power loss and frictional torque. Maximum decrease in frictional power loss and frictional torque is observed for partially grooving along 90°-360° region. The simulations are supported by proof-of-concept experimentation. Originality/value: This study is useful in the appropriate selection of groove parameters on bearing surface to the bearing performance characteristics.